Pengembangan Video Animasi Mengenal Pokok Pikiran Sebagai Media Pembelajaran di Sekolah Dasar - Shabira Khairunnisa Pratidina; Prana Dwija Iswara; Ani Nur Aeni (Elementary Teacher Education Program, Majalengka University, 2024)
This research is motivated by the fact that learning is still centered on the use of textbooks, causing students to be less interested in participating in learning, which affects students understanding, still confused in determining the location of the main ideas. The purpose of this research is to (1) explain the feasibility animated video Getting to Know the Main Ideas for fifth grade elementary school students, (2) determine the magnitude of the influence animated video Getting to Know the Main Ideas on the ability to determine the main ideas, and (3) analyze teacher and student assessments of the video animation Getting to Know the Main Ideas. The research method used is research and development with the ADDIE development model, namely Analysis, Design, Development, Implementation and Evaluation. Implemented for fifth grade elementary school students and teachers. Product feasibility was obtained from the validation with a feasibility percentage from material experts of 95% and a feasibility percentage from media experts of 78.4%. The magnitude of the effect was analyzed from the pretest and posttest results which were calculated using the paired samples test, showing a significance value of 0.000, less than 0.05. The product assessment results by teachers and students are in the range of 81-100% with very good criteria. Thus, the animated video Getting to Know the Main Ideas is suitable for use for learning, has a significant influence on the ability to determine the main ideas, and received a very good response from teachers and fifth grade elementary school students.